2022
DOI: 10.3389/fpls.2022.849048
|View full text |Cite
|
Sign up to set email alerts
|

Function Analysis of the ERF and DREB Subfamilies in Tomato Fruit Development and Ripening

Abstract: APETALA2/ethylene responsive factors (AP2/ERF) are unique regulators in the plant kingdom and are involved in the whole life activity processes such as development, ripening, and biotic and abiotic stresses. In tomato (Solanum lycopersicum), there are 140 AP2/ERF genes; however, their functionality remains poorly understood. In this work, the 14th and 19th amino acid differences in the AP2 domain were used to distinguish DREB and ERF subfamily members. Even when the AP2 domain of 68 ERF proteins from 20 plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…In addition, Liu et al (2006) indicated that Ala-37 was reported to play a key role in binding to both GCC-box and DRE, while Sun et al (2008) shown that the Ser-15 in the AP2/ERF domain was demonstrated to be essential for its specific binding to GCC-box. Recent studies showed that some other amino acids, such as Pro-9, His-9 and Ser-9, also have important functions Zhang L. et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…In addition, Liu et al (2006) indicated that Ala-37 was reported to play a key role in binding to both GCC-box and DRE, while Sun et al (2008) shown that the Ser-15 in the AP2/ERF domain was demonstrated to be essential for its specific binding to GCC-box. Recent studies showed that some other amino acids, such as Pro-9, His-9 and Ser-9, also have important functions Zhang L. et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…The AP2/ERF superfamily TFs have been identified in diverse plant species, including Arabidopsis thaliana [ 5 ], wheat ( Triticum turgidum ) [ 8 ], peanut ( Arachis hypogaea L.) [ 9 ], tomato ( Lycopersicon esculentum Miller) [ 10 ], common andrographis ( Andrographis paniculate ) [ 11 ], dark jute ( Corchorus olitorius L.) [ 12 ], and Chinese cherry ( Prunus pseudocerasus ) [ 13 ]. The AP2 subfamily binds to the GCAC(A/G)N(A/T)TCCC(A/G)ANG(C/T) element and has an essentially important impact on reproductive organ development, including the flower, ovule, spikelet, seed, floral organ identity, and meristem maintenance [ 2 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conserved amino acid analysis revealed that valine (V) is replaced by isoleucine (I) at the 14th position due to their same chemical structure, polarity, and characteristics in three Sl DREB genes. Both are aliphatic, non-polar, and hydrophobic, whereas glutamic acid (E) is being replaced by V, Q, D, H, L, and A at the 19th position ( Zhang et al, 2022 ). The genome-wide analysis discovered the presence of 58 Sl DREB genes, which can vary in numbers in different plants due to the variance in genome sizes and genes present in their genome.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes that were downregulated or not expressed under heat and drought stress might be involved in other abiotic stresses, developmental mechanisms, and the regulation of several stress-resistant genes involved in biotic responses. Previous studies on expression analysis exhibit the role of DREB genes in fruit development and ripening ( Zhang et al, 2022 ). Overall, the present study data illustrates the comprehensive interactive networks of Sl DREBs with various other stress-responsive proteins associated with the regulation of development, growth, and stress tolerance processes in tomato.…”
Section: Discussionmentioning
confidence: 99%